2018
DOI: 10.1016/j.cell.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Multiclonal Invasion in Breast Tumors Identified by Topographic Single Cell Sequencing

Abstract: Ductal carcinoma in situ (DCIS) is an early-stage breast cancer that infrequently progresses to invasive ductal carcinoma (IDC). Genomic evolution has been difficult to delineate during invasion due to intratumor heterogeneity and the low number of tumor cells in the ducts. To overcome these challenges, we developed Topographic Single Cell Sequencing (TSCS) to measure genomic copy number profiles of single tumor cells while preserving their spatial context in tissue sections. We applied TSCS to 1,293 single ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
328
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(352 citation statements)
references
References 62 publications
(71 reference statements)
21
328
2
1
Order By: Relevance
“…Our data showed that the lymph node metastasis likely was derived from a minor subclone of the InvF. Our data also suggest that the sequenced DCIS cells arose from a subclone and were not a precursor or a separate entity, an observation in line with another recent study (29). Further, single cancer cells located in areas of morphologically normal lymph nodes distant from the lymph node metastasis had gained additional mutations compared with single cells in the solid lymph node metastasis, indicating a case of a linear model of metastasis.…”
Section: Discussionsupporting
confidence: 79%
“…Our data showed that the lymph node metastasis likely was derived from a minor subclone of the InvF. Our data also suggest that the sequenced DCIS cells arose from a subclone and were not a precursor or a separate entity, an observation in line with another recent study (29). Further, single cancer cells located in areas of morphologically normal lymph nodes distant from the lymph node metastasis had gained additional mutations compared with single cells in the solid lymph node metastasis, indicating a case of a linear model of metastasis.…”
Section: Discussionsupporting
confidence: 79%
“…For the detection of CNVs in fetal cells, it is desirable to have the highest resolution possible, so that also (de novo) microdeletions/duplications are detected, such as the 2 to 3 Mb 22q11.2 deletion causing DiGeorge syndrome, the 1.5‐Mb deletion causing Williams syndrome or the 1.5‐Mb CMT1A duplication. Reliable CNV detection at 220 kb resolution has been described in single tumor cells by Casasent, Schalck , and Gao and a new WGA method reported by Chen et al, reported the detection of micro CNVs as small as 100 kb. From a clinical perspective, we believe that CNV detection at 0.5 Mb is a reasonable short‐term goal for cell‐based NIPT.…”
Section: Discussionmentioning
confidence: 99%
“…Because G&T-seq allowed us to extract and analyze DNA and RNA from the same tissue samples, we sought to validate the clonal assignment of our cell clusters and confirm the relationships among the CNV, SNV, and RNA clones identified. To visualize these relationships, we employed tanglegrams generated using the R package software Dendextend (Galili, 2015), whereby two phylogenetic trees are drawn opposite of each other, and auxiliary lines are used to connect corresponding cell clusters (Scornavacca et al, 2011, Casasent et al, 2018. Tanglegrams comparing the relationship between the CNV and SNV clones demonstrated that, with the exception of a single cell cluster, cell clusters designated as a CNV A, CNV B, or CNV C clone mapped to a corresponding SNV A, SNV B or SNV C clone (Fig.3B).…”
Section: G and T Sequencing Enables Direct Comparison Between Dna And Rmentioning
confidence: 99%